A PROSPECTIVE STUDY OF DRUG–DRUG INTERACTIONS AND ADVERSE DRUG REACTIONS AMONG STROKE PATIENTS IN A TERTIARY CARE HOSPITAL - Jith, Athira; Kumar, Chaithanya T; Joy, Joffey Sara; P, Kavitha Samy; R, Sambath Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Our study attempts to get an insight into the drug–drug interactions (DDIs) and adverse drug reactions (ADRs) among stroke patients from the Neurology Department in a private hospital. Methods: In a prospective study spanning 6 months (May to October 2015), we have analyzed the prescription data of 221 patients with both ischemic and hemorrhagic stroke. Gender, age, social habits, length of stay, drug utilization pattern, DDIs reported from the database and clinically observed, and ADRs of individual drugs were observed among the patients. Of 221 cases, 208 (94.11%) were ischemic, 12 (5.43%) were hemorrhagic, and 1 (0.45%) was transient ischemic attack. Results: A number of 140 patients were males and 80 were females. The mean age of the patients was between 41 and 70 years. In ischemic patients, 357 major, 282 moderate, and 38 mild DDIs were reported using a specific database, while in hemorrhagic patients, 10 major, 7 moderate, and 1 mild interaction were reported using a specific database. 18 DDIs were observed clinically and confirmed with evidence. 8 DDI-induced ADRs and 10 ADRs caused by individual drugs were observed in our study population. 18 DDIs were observed clinically and confirmed with evidence. 8 DDI-induced ADRs and 10 ADRs caused by individual drugs were observed in our study population. Conclusion: Drugs if wrongly prescribed may cause negative outcomes and pose significant challenge to health-care providers and may contribute to morbidity and mortality. Clinical pharmacist can play an important role in identifying and resolving drug-related problems through pharmaceutical care practices. Keywords: Stroke, Drug–drug interactions, Adverse drug reactions, Clinical pharmacist.